Identification and Characterization of the Heat-Induced Plastidial Stress Granules Reveal New Insight Into Arabidopsis Stress Response - Chodasiewicz, Monika; Sokolowska, Ewelina Maria; Nelson-Dittrich, Anna C.; Masiuk, Aleksandra; Beltran, Juan Camilo Moreno; Nelson, Andrew D. L.; Skirycz, Aleksandra (Frontiers in Plant Science, 2020)
Plants exhibit different physiological and molecular responses to adverse changes in their environment. One such molecular response is the sequestration of proteins, RNAs, and metabolites into cytoplasmic bodies called stress granules (cSGs). Here, we report that in addition to cSGs, heat stress also induces the formation of SG-like foci (pSGs) in the chloroplasts of the model plant Arabidopsis thaliana. Similarly to the cSGs, (i) pSGs assemble rapidly in response to stress and disappear when the stress ceases, (ii) pSG formation is inhibited by treatment with a translation inhibitor (lincomycin), and (iii) pSGs are composed of a stable core and a fluid outer shell. A previously published protocol for cSG extraction was successfully adapted to isolate pSGs followed by protein, metabolite, and RNA analysis. Analogously to the cSGs, pSGs sequester proteins essential for SG formation, dynamics and function, also including RNA-binding proteins with prion-like domain, ATPases and chaperones, and the amino acids proline and glutamic acid. However, the most intriguing observation relates to the pSG localization of proteins, such as a complete magnesium chelatase complex, which is involved in photosynthetic acclimation to stress. These data suggest that pSGs have a role in plant stress tolerance.